Modelling and assessment of the impact of supply disruption and cost of recovery using system dynamics approach. (26th July 2021) - Raghuram, P.; Harisankar, G.
Shorter product life cycles and customisation have exposed the hidden problems in the supply chain. Supply disruptions, caused due any sudden event, is one of the major concerns of the manufacturing industry. This paper focuses on the impact of non-availability of parts from a supplier due to unpredictable events and the cost of recovery from such disruption. System dynamics approach is used to model the interactions between the variables required to maintain the availability of parts. In this model, time to restore operations, time to find alternate suppliers, inventory consumption till restoration, safety stock availability and backlogs are considered. This model was then used to assess disruption impact on inventory, lead time and recovery costs using iThink software. Assessment of supply disruption for all the procured parts will help the company to recognise and take proactive steps, such as identifying alternate suppliers, making engineering changes and modifying the manufacturing processes.